Effect of wastewater particles on catalytic ozonation in the advanced treatment of petrochemical secondary effluent - Zhang, Siyu; Wu, Changyong; Zhou, Yuexi; Wang, Yaning; He, Xuwen (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •The effect of wastewater particles on catalytic ozonation was investigated.•Wastewater particles can increase the ozone consumption.•Ozone dosage lower than 10 mg L−1 cannot affect the particles characteristics.•Depletion rates of different components were characterized.•Removal of wastewater particles benefits the organic micro-pollutants removal. The effect of wastewater particles on catalytic ozonation during the treatment of petrochemical secondary effluent (PSE) was investigated. The dissolved organic carbon (DOC) removal results indicated that wastewater particles could significantly affect the catalytic oxidation reaction and increase ozone (O3) consumption. When the suspended solids (SS) was filtered by the 0.45 μm membrane, the O3 dosage to DOC removal ratio was 1.99 mgO3 mgDOC−1, while it increased to 2.99 mgO3 mgDOC−1 when the SS concentration was 50 ± 1.57 mg L−1. Wastewater particles can react with O3, thus reducing the O3 and hydroxyl radicals (OH) available for DOC removal. When the SS concentration was 30 ± 0.96 mg L−1, O3 dosages lower than 10 mg L−1 did not induce a change in the size and surface characteristics of the particles. Following the increase in the O3 dosage to 36 mg L−1, extracellular polymeric substances (EPS) reacted with O3/OH with different characteristics. Dissolved organic matter (DOM) had the highest depletion reaction rate, followed by the loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS). The average reaction rates of the three constituents were 1.44, 0.212, and 0.079 mg L−1 min−1, respectively. In addition, the results showed that eliminating wastewater particles would be beneficial for the removal of organic micro-pollutants (OMPs) by catalytic ozonation.